2000
DOI: 10.1097/00002030-200001070-00004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sites in HIV-1 reverse transcriptase associated with virological response to combination therapy

Abstract: Use of clinical data to analyse virological response to combination therapy has revealed effects of baseline amino acid mutations at sites not previously identified as being important in antiretroviral resistance. Predictors of long-term responses were different from those involved in the short term and may require more complex analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The results of several studies point to the potential significance of mutations at codons 44 and 118 in patients treated with nucleoside RT inhibitors (2,5,16,17). Our finding that the 44D/E and 118I mutations were more common in viruses from ZDV-and 3TC-treated patients is consistent with these results.…”
supporting
confidence: 89%
“…The results of several studies point to the potential significance of mutations at codons 44 and 118 in patients treated with nucleoside RT inhibitors (2,5,16,17). Our finding that the 44D/E and 118I mutations were more common in viruses from ZDV-and 3TC-treated patients is consistent with these results.…”
supporting
confidence: 89%
“…It is also possible that differences in the intracellular concentrations of nucleoside analog triphosphates and the deoxynucleoside triphosphate pool result in different selective pressures on RT (6). In addition, viral subtype and polymorphisms in RT that are not associated with drug resistance could influence the emergence of specific TAMs through mutational interactions (32).…”
Section: Vol 80 2006 Fitness Of Zidovudine-resistant Hiv-1 7023mentioning
confidence: 99%
“…The clinical benefits of antiretroviral treatment are limited by the selection of drug-resistant human immunodeficiency virus type 1 (HIV-1) strains during therapy (38). A recent U.S. survey reported that up to 70% of patients with detectable plasma viremia harbor drug-resistant viral variants (D. Richman, S. Bozzette, S. Morton, S. Chien, T. Wrin, K. Dawson, and N. Hellmann, Abstr.…”
mentioning
confidence: 99%